Physical chemistry - Levine, Ira.N (New Delhi Tata Mcgraw Hill Education, 2011)
The sixth edition of Physical Chemistry provides students with an in-depth fundamental treatment of physical chemistry. At the same time, the treatment is made easy to follow by giving full step-by-step derivations, clear explanations and by avoiding advanced mathematics unfamiliar to students. Necessary math and physics have thorough review sections. Worked examples are followed by a practice exercise. Key Features: Additional homework problems testing the qualitative understanding of physical chemistry content has been integrated into this edition The in-chapter examples are written to lead the student to a clearly worked-out answer Table of Contents: 1 Thermodynamics 2 The First Law of Thermodynamics 3 The Second Law of Thermodynamics 4 Material Equilibrium 5 Standard Thermodynamic Functions of Reaction 6 Reaction Equilibrium in Ideal Gas Mixtures 7 One-Component Phase Equilibrium and Surfaces 8 Real Gases 9 Solutions 10 Nonideal Solutions 11 Reaction Equilibrium in Nonideal Systems 12 Multicomponent Phase Equilibrium 13 Electrochemical Systems 14 Kinetic Theory of Gases 15 Transport Processes 16 Reaction Kinetics 17 Quantum Mechanics 18 Atomic Structure 19 Molecular Electronic Structure 20 Spectroscopy and Photochemistry 21 Statistical Mechanics 22 Theories of Reaction Rates 23 Solids and Liquids.
Keywords: chemistry,physical chemistry